Large increase in fracture resistance of stishovite with crack extension less than one micrometer - Yoshida, Kimiko (Sci Rep, 2015)
The development of strong, tough, and damage-tolerant ceramics requires nano/microstructure design to utilize toughening mechanisms operating at different length scales. The toughening mechanisms so far known are effective in micro-scale, then, they require the crack extension of more than a few micrometers to increase the fracture resistance. Here, we developed a micro-mechanical test method using micro-cantilever beam specimens to determine the very early part of resistance-curve of nanocrystalline SiO(2) stishovite, which exhibited fracture-induced amorphization. We revealed that this novel toughening mechanism was effective even at length scale of nanometer due to narrow transformation zone width of a few tens of nanometers and large dilatational strain (from 60 to 95%) associated with the transition of crystal to amorphous state. This testing method will be a powerful tool to search for toughening mechanisms that may operate at nanoscale for attaining both reliability and strength of structural materials.